Typing of clinical herpes simplex virus isolates with mouse monoclonal antibodies to herpes simplex virus types 1 and 2: comparison with type-specific rabbit antisera and restriction endonuclease analysis of viral DNA. - Peterson, E (1983)
A total of 122 clinical isolates of herpes simplex virus (HSV) from 107 patients were typed by using an indirect immunoperoxidase technique with commercially available type-specific rabbit antisera, recently developed mouse monoclonal antibodies to HSV types 1 and 2, and restriction endonuclease analysis of viral DNA. With the commercially available type-specific rabbit antisera, 34% of clinical HSV isolates were of indeterminate type; 63% of them were typed as HSV type 1 and 37% as HSV type 2 by using monoclonal antibody and restriction enzyme typing systems. Typing by immunofluorescence assay with the monoclonal antibodies gave identical results to those obtained by restriction enzyme analysis. Simultaneous infection with both HSV types was demonstrated by monoclonal antibody typing in five isolates from three patients. These findings were subsequently confirmed by plaque purification and restriction endonuclease analysis of viral DNA. Monoclonal antibodies were as sensitive as restriction enzyme analysis for the typing of clinical HSV isolates. Because of their simplicity, they are more amenable to use in clinical laboratories than is restriction endonuclease analysis.